Pilot scale microbial production and optimization of Serratia peptidase from Serratia marcescens - Subbaiya, R; Ayyappadasan, G; Mythili, S V; Dhivya, E; Ponmurugan, P (Journal of Ecobiotechnology, 2012)
Serratia peptidase is active proteolytic enzyme which has the potential of cleaving peptide bond. Present investigation deals about the Microbial production of serratia peptidase using Serratia marcescens in small scale fermentor. Batch fermentor has been run continuously throughout the night to analyze the production of protein as well as kinetics. Culture broth was maintained at 150rpm for 72 hrs. Protein sample was isolated by centrifuging at 3000rpm for 10mints. The result revealed that Serratia marcescens showed the enormous production of protein in fed batch fermentor compared to the small scale level. Different substrates were been used for the production of enzyme. Among all cysteine showed the better activity as 2 units/ml of enzyme. Enzymatic assay of Serratia peptidase was done at different time interval of crude broth. Enzyme activity showed that maximum at 40ºC for 72hrs. It was observed that 0.65 units/ml of enzyme. Fed batch pilot scale production of Serratia peptidase was done at 0.5%cystein and 700rpm for 48hrs of run time.